A vibrational technique for diagnosing loosened total hip endoprostheses: An experimental sawbone study - Rieger, Johannes Sebastian; Jäger, Sebastian; Schuld, Christian; Kretzer, Jan Philippe; Bitsch, Rudi G. (Medical engineering & physics, 2013)
Aseptic loosening of hip implants is a severe orthopaedic problem and a valid diagnosis is often difficult. A potential method to determine loosening of the prosthesis is a swing analysis of the bone-implant interface using a vibrational technique. In this study, hip models were constructed to assess the vibration behaviour of the stem and cup components. Four different states of implant loosening were simulated: (1) stem and cup stable, (2) stem loosened and cup stable, (3) stem and cup loosened, and (4) stem stable and cup loosened. The model was excited at the lateral condyle of the femur between 100Hz and 2000Hz. Resonance spectra were recorded using an optical laser vibrometer and an accelerometer-based system. Analysis of the spectra revealed shifts of the resonances towards lower frequencies, especially in the case of a loosened stem component. The integral value of the spectra was a second parameter that was sensitive to a stem loosening. In the case of a loosened cup, a peak count analysis resulted in a significantly higher number of counts. In our model, different states of implant loosening could be determined with a vibrational technique and the localisation of the loosened component could be distinguished as well.
Available online 4 June 2012
Available online 4 June 2012
Gesehen am 21.06.2018